Microbial Communities in Cultural Heritage and Their Control - De Leo, Filomena; Jurado, Valme (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cultural heritage plays a key role in understanding the history of humankind; therefore, the adoption of appropriate strategies for its conservation is essential. Microorganisms, such as bacteria, fungi and microalgae, which are usually organized on the surface in microbial communities as "biofilms", can cause serious problems in the conservation of cultural heritage, making the adoption of prevention and conservation strategies a critical issue. This editorial focuses on studies published within the present Special Issue that present advances in the field of the biodeterioration of cultural heritage caused by microbial communities, with a particular focus on new methods for their elimination and control.